2010
DOI: 10.1007/s00440-010-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and position of the farthest peaks of a family of stochastic heat and wave equations

Abstract: We study the stochastic heat equation ∂ t u = Lu + σ(u)Ẇ in (1 + 1) dimensions, whereẆ is space-time white noise, σ : R → R is Lipschitz continuous, and L is the generator of a symmetric Lévy process that has finite exponential moments, and u 0 has exponential decay at ±∞. We prove that under natural conditions on σ: (i) The νth absolute moment of the solution to our stochastic heat equation grows exponentially with time; and (ii) The distances to the origin of the farthest high peaks of those moments grow exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 29 publications
12
78
0
Order By: Relevance
“…Thus, we are left to consider exponents in the region p ∈ (1, 1 + 2/d). In dimension 1, we can use Itô's isometry to calculate second moments, and there are essentially no differences to the estimates (or exact formulae) obtained in the Gaussian case ( [9,12,17]). However, for d ≥ 2, we cannot use Itô's isometry because p is strictly between 1 and 2.…”
Section: The Martingale Casementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we are left to consider exponents in the region p ∈ (1, 1 + 2/d). In dimension 1, we can use Itô's isometry to calculate second moments, and there are essentially no differences to the estimates (or exact formulae) obtained in the Gaussian case ( [9,12,17]). However, for d ≥ 2, we cannot use Itô's isometry because p is strictly between 1 and 2.…”
Section: The Martingale Casementioning
confidence: 99%
“…In particular, we are interested in conditions under which the solution Y to (1.5) exhibits the phenomenon of intermittency. The following definition follows [7], Definition III.1.1, [12], Equations (1.6) and (1.7), and [20], Definition 7.5. Definition 1.1 Let Y be the mild solution to (1.5) and p ∈ (0, ∞).…”
Section: Introductionmentioning
confidence: 99%
“…Let u ∈ L 2 (Ω; H) and (u n ) n≥1 ⊂ Dom δ such that E u n − u 2 H → 0. Suppose that there exists a random variable G ∈ L 2 (Ω) such that E(δ(u n )F ) → E(GF ) for all F ∈ S, where S is the class of smooth random variables of form (7). Then u ∈ Dom δ and δ(u) = G.…”
Section: Intermittencymentioning
confidence: 99%
“…Recently, there has been a lot of interest in studying the intermittency property of solutions to stochastic partial differential equations, such as the stochastic heat and wave equations. For the former, we refer the reader to [5,7,13,6,17]. On the other hand, intermittency for the solution of the stochastic wave equation driven by a noise which is white in time and has a smoother space correlation than the one considered here was studied in [10,8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in Section 6 we study the speed of propagation of intermittent peaks. The propagation of the farthest high peaks was first considered by Conus and Khoshnevisan in [7] for a one-dimensional heat equation driven by a space-time white noise with compactly supported initial condition, where it is shown that there are intermittency fronts that move linearly with time as λt. More precisely, they defined the lower and upper exponential growth indices as follows:…”
Section: Introductionmentioning
confidence: 99%